A new handsome fungus beetle of the subfamily Endomychinae (Coccinelloidea: Endomychidae) from Baltic amber of the Sambian Peninsula - Alekseev, Vitalii; Tomaszewska, Wioletta (Zootaxa, 2025)
Based on an inclusion in Baltic amber, the first extinct species of the genus Danae Reiche and the second species of the subfamily Endomychinae from the Eocene is described and illustrated. The new fossil species, D. sembanata sp. nov., is compared with related extant and morphologically close extinct taxa. General rarity of endomychid specimens in Baltic amber is briefly discussed.